2022
DOI: 10.1186/s12887-022-03319-w
|View full text |Cite
|
Sign up to set email alerts
|

Pain and pain management in children and adolescents receiving hospital care: a cross-sectional study from Sweden

Abstract: Background Pain is a common symptom in children receiving hospital care. Adequate pain management in paediatric patients is of the utmost importance. Few studies have investigated children’s own experiences of pain during hospitalization. Aim To describe the prevalence of pain, self-reported pain intensity at rest and during movement, pain management and compliance with pain treatment guidelines in children and adolescents receiving hospital care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Further, in a study of almost one million American children with appendicitis, less than 60% received any analgesia, and less than 40% received opioid analgesia, for a condition which is known to cause moderate-to-severe pain [ 9 ]. This undertreatment exists despite a wide base of evidence that is available to be implemented into practice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, in a study of almost one million American children with appendicitis, less than 60% received any analgesia, and less than 40% received opioid analgesia, for a condition which is known to cause moderate-to-severe pain [ 9 ]. This undertreatment exists despite a wide base of evidence that is available to be implemented into practice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For all hospital health workers, in addition to the commitment to continuing education, it would be necessary to focus attention also on effective and safe use of drugs, especially opioids, alongside an intensification of psychological therapy, non-drug therapy and set up courses for parents and children [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could have facilitated the decision-making process for children in pain and could have increased nurses' confidence regarding pain management [41]. For all hospital health workers, in addition to the commitment to continuing education, it would be necessary to focus attention also on effective and safe use of drugs, especially opioids, alongside an intensification of psychological therapy, non-drug therapy and set up courses for parents and children [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…35,37,40 It is further suggested that pain should be assessed both at rest and with movement. 22 Previous study found that pediatric hospital pain management guidelines are not always closely followed. 19 Fortunately, many pediatric hospitals now have acute pain services.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Up to three quarters of hospitalized children also report having moderate to severe pain, with significant pain arising from common procedures, such as blood draws and peripheral intravenous line placement. [14][15][16][17][18][19][20][21][22] While consequences of elevated pain are less well studied in children, inadequate analgesia clearly has negative consequences. Children who undergo procedures with insufficient analgesia have an increased risk of poor pain management for subsequent procedures, even when adequate analgesic is utilized, 23,24 and preterm neonates on ventilatory support who receive greater amounts of analgesics have better neurological outcomes than those who receive lower doses.…”
Section: Introductionmentioning
confidence: 99%